Assessment of the impact of crop management strategies on the yield of early-maturing maize varieties in the drylands of Niger Republic: Application of the DSSAT-CERES-Maize model - Kamara, A.; Garba, M.; Tofa, A.; Mohamed, A.M.L.; Souley, A.M.; Abdoulaye, T.; Kapran, B.I. (Elsevier, 2023)
Maize is increasingly becoming important in Niger for use as food and feed. Production is however, faced with several abiotic and biotic constraints. Researchers have developed early-maturing maize varieties that are tolerant to drought, the parasitic weed Striga hermonthica and diseases that fit into the short growing production environment. The evaluation and deployment of these varieties would, however, involve costly and time-consuming field trials across the maize production zones of the country. The CERES-Maize model was applied to assess the performance of two early-maturing maize varieties under varying planting windows and nitrogen application in three agroecological zones of the country. The model was calibrated with datasets collected from field trials conducted under optimal conditions (supplementary irrigation and full nutrient supply) at three locations in northern Nigeria. The model was validated with independent data set obtained from field trials conducted in 2020 and 2021 at 4 locations in the Republic of Niger under rainfed conditions. For each variety the treatments were five nitrogen (N) rates (0, 30, 60, 90 and 120 kg ha− 1). The results from model calibration and validation revealed that the model accurately reproduced the observed value for days to flowering, physiological maturity, aboveground dry biomass and grain yield with low nRMSE (0.4–12.7%) and high d-index (0.70–0.99) for both varieties. The long-term simulation results (1985–2020) showed that the maize performance was dependent on location, planting window and nitrogen rates. The variety 2014 TZE-Y yielded higher than Brico in all locations for all treatments because it takes longer to mature and accumulate higher dry matter and have higher number of kernels. Simulated yields were generally higher in the Sudan savanna agroecological zone than in the other zones because of higher rainfall and higher clay content of the soil in this zone. The response to N application was influenced by planting window in each agroecological zone. With the exception of two sites, grain yield declined with planting beyond July 14 (PW3) and response to N was not significant beyond this date in the Sudan savanna agroecological zone. Grain yield declined with planting beyond July 7 in the Sahel and Sudan Sahel agroecological zones. There was no further response to N beyond 30 and 60 kg N ha− 1 when planting is delayed beyond July 7 in the Sahel and Sahel-Sudan agroecological zones, respectively.